Analysis of Synaptotagmin, SV2, and Rab3 Expression in Cortical Glutamatergic and GABAergic Axon Terminals - Bragina, Luca; Fattorini, Giorgia; Giovedì, Silvia; Melone, Marcello; Bosco, Federica; Benfenati, Fabio; Conti, Fiorenzo (Frontiers in Cellular Neuroscience, 2012)
We investigated whether cortical glutamatergic and GABAergic release machineries can be differentiated on the basis of the nature and amount of proteins they express, by performing a quantitative analysis of the degree of co-localization of synaptotagmin (SYT) 1 and 2, synaptic vesicle protein 2 (SV2) A and B, and Rab3a and c in VGLUT1+, VGLUT2+, and VGAT+ terminals and synaptic vesicles in rat cerebral cortex. Co-localization studies showed that SYT1 was expressed in 60% of VGLUT1 and VGLUT2 puncta and 50% of VGAT puncta; SYT2 in 30% of VGLUT1 and VGLUT2 puncta, and in 80% of VGAT puncta; SV2A in 80% of VGLUT1, 40% of VGLUT2, and >90% of VGAT puncta; SV2B in 90% of VGLUT1, 45% of VGLUT2, and 15% VGAT puncta; Rab3a in 80% of VGLUT1, 40% in VGLUT2, and 60% in VGAT puncta; and Rab3c in 20% VGLUT1, 40% VGLUT2, and 60% in VGAT puncta. None of the proteins studied exhibited a differential laminar distribution. Since SV2B is reportedly expressed by glutamatergic neurons and we observed SV2B expression in VGAT puncta, we performed electron microscopic studies and found SV2B positive axon terminals forming symmetric synapses. Immunoisolation studies showed that the expression levels of the protein isoforms varied in the three populations of SVs. Expression of SYT1 was highest in VGLUT1-SVs, while SYT2 expression was similar in the three SV groups. Expression of SV2A was similarly high in all three SV populations, except for SV2B levels that were very low in VGAT-SVs. Finally, Rab3a levels were similar in the three SV groups, while Rab3c levels were highest in VGLUT1-SVs. These quantitative results extend our previous studies on the differential expression of presynaptic proteins involved in neurotransmitter release in GABAergic and glutamatergic terminals and indicate that heterogeneity of the respective release machineries can be generated by the differential complement of synaptic vesicle proteins involved in distinct stages of the release process.